Fischer-Tropsch process from synthesis gas over fe-co/HZSM-5 catalyst to produce biofuel. (December 2019) - Roesyadi, A; Jimmy,; Ihsanti, D H; Nuraini, A
Abstract: Fischer-Tropsch synthesis is the process of converting hydrogen into liquid fuel through several stages, namely: polymerization of CO and H2 gases into long chain hydrocarbons. From the FT process that requires many of these steps, this research was carried out in order to be able to simplify the Fischer-Tropsch process through limited polymerization to obtain liquid fuels. By combining Co and Fe metal catalysts, it is expected to show better performance than the use of individual metals. Using a Fe-Co/HZSM-5 metal catalyst combination in a fixed bed reactor at a reaction temperature of 225°C. Fe-Co / HZSM-5 catalyst was made by wet impregnation, then Fe-Co/HZSM-5 catalyst was characterized using XRD, BET, and SEM-EDX. From the XRD results, the addition of Fe and Co did not change the crystal structure of the HZSM-5 catalyst. The surface area of the HZSM-5 was 526.03 m 2 /g and decreased after the addition of metal (Fe and Co) to the HZSM-5. This change indicates that Fe and Co particles were successfully dispersed on the surface of the HZSM-5 and inserted into the HZSM-5 pore. Hydrocarbon biofuel products are analyzed using GC-MS. The results of GC-MS hydrocarbon products showed the highest compounds for hydrocarbons C13 and C14 chains were 5.78% and 6.68% at 225 °C.